WEIGHTED APPROXIMATION IN UNIFORM NORM BY MEYER-K¨ONIG AND ZELLER OPERATORS - Gadjev, Ivan; E. Parvanov, Parvan (Annual of Sofia University St. Kliment Ohridski. Faculty of Mathematics and Informatics, 2017)
The weighted approximation errors of $Meyer-K\ddot{o}nig$ and $Zeller$ operator is characterized for weights of the form $w(x) = x^{γ_0}(1 − x)^{γ_1} $, where $γ_0 \in [−1, 0], γ_1 \in \mathbb{R}$. Direct inequalities and strong converse inequalities of type A are proved in terms of the weighted $K$-functional.